(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2023)
The article discusses in detail the possibilities of automating the process of processing projects and structural documents of buildings and construction structures, methods of design using modern computer technologies, computer design of construction structures, structural mechanics and construction structures.